Why is it important to study political elites? - Perissinotto, Renato Monseff (2020)
The article reviews classic works and defends the theoretical usefulness of studies that seek to understand the elites as a way of comprehending important aspects of the political reality. In the results, three dimensions are emphasized: 1) the design of political institutions and of the economic structure, also considering the role of those who actually take part in elaborating the policy; 2) the recognition that political elites, however autonomous they may be, operate under objective conditions, which limit their choices or shape their values; and 3) the perception that the search for power is linked to the very definition of an political elite, which does not mean that this is the only aspect to be analyzed in a study on the topic.